ORIENTASI BIMBINGAN DAN KONSELING DI SEKOLAH DASAR DALAM MENDUKUNG PERKEMBANGAN PESERTA DIDIK - Safitri, Ayu; Sunarti, Titi; Karimah, Irodati; Tarsih, Tarsih; Sapriyah, Alda (Universitas Negeri Medan, 2025)
Guidance and counseling orientation is a fundamental service that plays an important role in helping elementary school students recognize the school environment, understand school rules, and adjust psychologically, socially, and academically. Given that young learners are at a precarious developmental juncture, they often encounter significant adaptive hurdles, necessitating systematic and sustained intervention. This study aims to theoretically examine the implementation of guidance and counseling orientation in elementary schools and its role in supporting student development. The research method employed is a literature review by analyzing relevant books and national and international journal articles. The synthesized findings indicate that orientation programs, when executed in an integrated manner, significantly bolster student readiness and environmental adaptation. In addition, orientation services contribute to the prevention of emotional and social problems among students. Consequently, it is imperative to design these services as an inseparable core of the primary education framework.